PENGEMBANGAN BUKU KUMPULAN CERITA ANAK DAERAH LAMONGAN UNTUK MENINGKATKAN KARAKTER SISWA SD - Sriati Sriati (MEDIA DIDAKTIKA, 2017)
The purpose of the research development of the Regional Children's story book Lamongan set were (1) to describe the process of the development of the Regional Children's story book at Lamongan to Improve the students in elementary school; (2) describe the quality of the Regional Children's story book at Lamongan, (3) to Improve the students in elementary school’s character developed, based on (a) the appropriateness of content, (b) the feasibility of presentation, (c) the feasibility of the language, (d) the feasibility of graphic; (3) describe the implementation storybook developed, including (a) the teachers’ activities, (b) students’ activities, (c) the students’ achievement, (d) the supporting factors, and (e) limiting factor when implementing the Regional Children's story book at Lamongan. The research was the development study . The results of the research was a products of Children's story book Lamongan which had been developed consisting of three phases, (1) the definition (2) designing and (3) development. Instruments used to collect the data included validation sheet (expert Indonesian, learning experts Indonesian, Indonesian teacher, and expert graphic),